Pengaruh Beban Kerja dan Stres Kerja terhadap Kinerja Perawat melalui Kualitas Pelayanan Keperawatan di Puskesmas Bluto, Kabupaten Sumenep - Kartono Kartono; Rusdiyanto Rusdiyanto; Woro Utari (Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of workload and work stress on nurse performance by considering the role of nursing service quality as a mediating variable. The study was conducted at the Bluto Health Center, Sumenep Regency, which is one of the first-level public health service centers in the area. The research method used a quantitative approach with an explanatory design. A total of 37 nurses became research respondents. Data were collected through structured questionnaires and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique. The results showed that workload had a significant positive effect on the quality of nursing services (coefficient 0.461; p = 0.001) and nurse performance (coefficient 0.343; p = 0.003). Conversely, work stress had a significant negative impact on the quality of nursing services (coefficient -0.362; p = 0.02) but did not have a significant direct effect on nurse performance (coefficient -0.129; p = 0.290). In addition, the quality of nursing services is proven to have a significant positive effect on nurse performance (coefficient 0.526; p = 0.000). Furthermore, the quality of nursing services is proven to mediate the relationship between workload and work stress on performance. Workload increases performance through service quality (coefficient 0.243; p = 0.020), while work stress decreases performance through the same pathway (coefficient -0.191; p = 0.040). This study emphasizes the importance of managing workload and stress to improve nurse performance through improving the quality of nursing services.